(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The article deals with the use of judicial sources in the study of the mafias, by proposing some notes in order to stimulate debate on an issue that so far has not been systematically analyzed in the social sciences. First of all, it explores the reasons for the lack of a systematic reflection on the use of judicial sources in the study of the mafias within social sciences subsequently; then it underlines the importance of using a non-anonymized personal data in the study of the mafia phenomenon; and, finally, it maintains that in the field of researches on mafias and corruption it is more important the right to memory rather than the right to privacy. Keywords: mafias, judiciary sources, memory, privacy, oblivion